The Impact of Regional Development Bank Performance on MSME Credit in Indonesia (2014 – 2023) - Amanda Pratiwi Rizal; Heni Hasanah; Mutiara Probokawuryan (School of Business, IPB University (SB-IPB), 2026)
Background: Micro, Small, and Medium Enterprises (MSMEs) are a major pillar of Indonesia’s economy, yet their access to formal financing remains limited. Regional Development Banks (BPDs) are expected to strengthen MSME financing because of their regional mandate and proximity to local economic actors, but their contribution to national MSME credit is still relatively small.Purpose: This study aims to analyze the effect of BPD on MSME credit in Indonesia and to examine whether the number of micro and small industries moderates this relationship.Design/methodology/approach: This study applies descriptive analysis and panel data regression to 15 conventional BPDs operating in single provinces during 2014–2023. MSME credit distribution at the provincial level is analyzed using bank performance indicators, regional macroeconomic variables, a COVID-19 dummy, and the interaction between net interest margin and the number of micro and small industries.Findings/Results: Capital adequacy, net interest margin, and loan-to-deposit ratio positively affect MSME credit, while return on assets has a negative effect. Gross regional domestic product (GRDP) and the number of micro and small industries increase MSME credit, but the micro prime lending rate reduces it, and the moderating effect of micro and small industries weakens the role of net interest margin.Conclusion: MSME credit distribution is shaped not only by internal bank performance but also by regional economic conditions and the affordability of credit. Strengthening MSME financing requires sound bank performance, efficient intermediation, and more accessible lending costs.Originality/value (State of the art): This study specifically focuses on Regional Development Banks (BPDs), covers the 2014–2023 period, combines internal bank and external regional variables, and introduces the number of micro and small industries as a moderating variable in explaining MSME credit distribution. Keywords:regional development banks, msme credit, BPD, panel data, Indonesia